2007
DOI: 10.1037/0882-7974.22.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Does a time-monitoring deficit influence older adults' delayed retrieval shift during skill acquisition?

Abstract: Abstract:The authors evaluated age-related time-monitoring deficits and their contribution to older adults' reluctance to shift to memory retrieval in the noun-pair lookup (NP) task. Older adults (M = 67 years) showed slower rates of response time (RT) improvements than younger adults (M = 19 years), because of a delayed strategy shift. Older adults estimated scanning latencies as being faster than they actually were and showed poor resolution in discriminating short from long RTs early in practice. The differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 50 publications
5
47
2
3
Order By: Relevance
“…Compared to younger adults, older adults self-select practice strategies requiring minimal cognitive effort (e.g., recognition) for word association tasks and novel arithmetic problems compared to the cognitively effortful strategies (e.g., retrieval) considered advantageous for learning (D'Eredita & Hoyer, 2010;Hertzog, Touron, & Hines, 2007;Rogers & Gilbert, 1997;Rogers, Hertzog, & Fisk, 2000;Touron & Hertzog, 2004a, 2004bTouron, Hoyer, & Cerella, 2004). Older adults' propensity to individualize a learning context that places low demands on their cognitive processes not only results in a less than favorable learning context but also suggests an explicit awareness of their age-related changes to information processing abilities and working memory capacity (Bäckman, Lindenberger, Li, & Nyberg, 2010;Bäckman et al, 2000;Fjell & Walhovd, 2010;Luo & Craik, 2008;Salthouse, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…Compared to younger adults, older adults self-select practice strategies requiring minimal cognitive effort (e.g., recognition) for word association tasks and novel arithmetic problems compared to the cognitively effortful strategies (e.g., retrieval) considered advantageous for learning (D'Eredita & Hoyer, 2010;Hertzog, Touron, & Hines, 2007;Rogers & Gilbert, 1997;Rogers, Hertzog, & Fisk, 2000;Touron & Hertzog, 2004a, 2004bTouron, Hoyer, & Cerella, 2004). Older adults' propensity to individualize a learning context that places low demands on their cognitive processes not only results in a less than favorable learning context but also suggests an explicit awareness of their age-related changes to information processing abilities and working memory capacity (Bäckman, Lindenberger, Li, & Nyberg, 2010;Bäckman et al, 2000;Fjell & Walhovd, 2010;Luo & Craik, 2008;Salthouse, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…In doing single-digit multiplication, for example, children may initially perform a repeated addition algorithm, but with sufficient practice will transition to direct retrieval (e.g., Siegler, 1988). Multiple laboratory studies have confirmed this shift over a variety of arithmetic and nonarithmetic tasks (Delaney, Reder, Staszewski & Ritter, 1998;Hertzog, Touron & Hines, 2007;Jenkins & Hoyer, 2000;Logan, 1988Logan, , 1992Onyper, Hoyer & Cerella, 2006;Palmeri, 1997;Rawson, 2004;Reder & Ritter, 1992;Rickard, 1997Rickard, , 1999Rickard, , 2004Rickard & Bajic, 2003Rogers, Hertzog & Fisk, 2000;Schunn, Reder, Nhouyvanisvong, Richards & Stroffolino, 1997;Touron, Hoyer & Cerella, 2001). An understanding of the temporal dynamics of strategy execution in these tasks is integral to the broader goal of modeling the underlying learning processes and performance mechanisms, as well as the factors that may modulate the rate of the strategy shift (e.g., Bourne, Raymond & Healy, 2010;Onyper et al, 2006;Salvucci & Taatgen, 2008;Touron & Hertzog, 2009).…”
mentioning
confidence: 99%
“…An example laboratory task is noun-pair lookup (Hertzog et al, 2007;Touron et al, 2001). In a typical version of that task, a set of noun pairs is presented at the top of the screen.…”
mentioning
confidence: 99%
“…Despite the small number of problems and the large number of practice trials, reports of retrieval use were still lower for older adults than for younger adults at the end of practice. Other studies have also shown persistent age differences in memory-based automaticity even after extensive practice with the same items (e.g., Hertzog, Touron, & Hines, 2007;Jenkins & Hoyer, 2000;Lamson & Rogers, 2008;Touron, 2006). For example, Touron and Hertzog (2004a) found persistent age differences in retrieval use after 60 item repetitions, even in a condition for which all items were pretrained.…”
Section: Age Differences In Memory-based Automaticitymentioning
confidence: 97%